THE READABILITY LEVEL OF READING TEXTS IN ENGLISH FINAL EXAM TEST FOR NINTH GRADE STUDENTS AT SMP BEREA TONDANO - Theresia Tesalonika Polii; Noldy Pelenkahu; Paula Hampp (Program Studi Pendidikan Bahasa Inggris, 2022)
Reading is one of the language components that English learners must be familiar with. Reading is the act of extracting meaning from written text. Readers use their understanding of the writing system, language, and the capacity to deduce meaning from text. The aim of this research was to find out the readability level of reading texts of English final exam test for ninth grade students at SMP Berea Tondano. The writer analyzed 3 past final exam test. The writer used Flesch Reading Ease Formula to analyzed the test. The data was categorized in 5 level of readability. After analyzing the collected data, the writer found 1 text or (3.8%) in level very easy, 8 texts or (30.8%) in level easy, 7 texts or (26.9%) in level fairly easy, 7 texts or (26.9%) in level standard, and 3 texts or (11.5%) in level fairly difficult. Based on the collected data, 7 reading texts or (26.9%) were found in standard level, and the writer concluded that the test was suitable for the ninth grade students